1998
DOI: 10.1046/j.1365-2540.1998.00375.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of esterase-mediated insecticide resistance in the aphid Schizaphis graminum

Abstract: The genetics of organophosphate resistance, including the pattern of inheritance and the underlying genetic mechanism, were investigated in the aphid Schizaphis graminum (the greenbug). Resistant greenbugs with pattern 1 (R1) and pattern 2 (R2) esterase and susceptible (S) greenbugs were induced into the sexual cycle and crossed. Each resistance-associated esterase pattern in the greenbug was inherited in a Mendelian fashion as a single gene. An aphid clone that displayed both resistance-associated esterase pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 13 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…They suggest that the three esterases are products of a single gene, and the different electromorphs were the result of protease digestion (Chen & Sun, 1994). Other species where organophosphate resistance has been linked to increased esterase enzyme activities are red scale (Grafton‐Cardwell et al ., 1998), sibling species A, B and C of Anopheles culicifacies (Raghavendra et al ., 1998) and the aphid, Schizaphis graminum (Rider et al ., 1998). Esterase‐associated resistance may result from a number of potential mechanisms, including production of a more efficient enzyme (Beeman & Schimidt, 1982; Matsumura & Voss, 1965), a gene duplication of an existing enzyme coding gene such as E4 (esterase‐4) in Myzus persicae (Field & Devonshire, 1992), or to evolution of an existing enzyme‐coding gene that produces a variant of that enzyme, that is, the duplicated FE4 variant or E4 in M. persicae (Devonshire, 1989; Devonshire & Field, 1991; Field & Devonshire, 1992; Field et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…They suggest that the three esterases are products of a single gene, and the different electromorphs were the result of protease digestion (Chen & Sun, 1994). Other species where organophosphate resistance has been linked to increased esterase enzyme activities are red scale (Grafton‐Cardwell et al ., 1998), sibling species A, B and C of Anopheles culicifacies (Raghavendra et al ., 1998) and the aphid, Schizaphis graminum (Rider et al ., 1998). Esterase‐associated resistance may result from a number of potential mechanisms, including production of a more efficient enzyme (Beeman & Schimidt, 1982; Matsumura & Voss, 1965), a gene duplication of an existing enzyme coding gene such as E4 (esterase‐4) in Myzus persicae (Field & Devonshire, 1992), or to evolution of an existing enzyme‐coding gene that produces a variant of that enzyme, that is, the duplicated FE4 variant or E4 in M. persicae (Devonshire, 1989; Devonshire & Field, 1991; Field & Devonshire, 1992; Field et al ., 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This high esterase activity was shown to be correlated to organophosphate resistance in brown planthoppers of rice (Chen and Sun 1994;Hemingway et al 1999). Among other species where organophosphate resistance is associated with increased esterase enzyme activity are sibling species A, B, and C of Anopheles culicifacies (Raghavendra et al 1998) and the aphid Schizaphis graminum (Rider et al 1998). Esterase-associated resistance may be due to the production of a more efficient enzyme (Beeman and Schmidt 1982), or to a gene duplication of an existing enzyme coding gene such as E4 (esterase-4) in Myzus persicae (Field and Devonshire 1992), or to the evolution of an existing enzyme-coding gene to produce a variant of that enzyme, i.e.…”
Section: Amovamentioning
confidence: 99%
“…Current recommendations to manage the evolution of insecticide resistance rely on theoretical predictions based on spatially explicit, single‐ or two‐locus population genetic models, which assume that resistance alleles occur at low frequency in pest populations prior to pesticide exposure due to recent origin or fitness costs in the absence of selection (Caprio & Tabashnik, ; Gould, Kennedy, & Johnson, ; Mallet, ; Mallet & Porter, ; Rosenheim & Tabashnik, ; Roush & McKenzie, ; Tabashnik et al., ). While most studies on the genetic basis of insecticide resistance have concluded that adaptation to insecticides is monogenic and drawing from rare alleles (Beeman, ; Brown, ; Crowder et al., ; Georghiou, ; Halliday & Georghiou, ; Hart, ; Oppenoorth, ; Rider, Wilde, & Kambhampati, ; Roush & Tabashnik, ; Roush et al., ; Shanahan, ; Shetty, Sanil, & Shetty, ; White & Bell, ; Wirth, Walton, & Federici, ), inferences could be improved by integrating data from a broader sample of pest populations and genomes (Wellenreuther & Hansson, ).…”
Section: Introductionmentioning
confidence: 99%